Evaluation of paternities with less usual data using Bayesian Networks - Andrade, M.; Ferreira, M. A. M. (International Conference on Biomedical Engineering and Informatics, BMEI 2010, 2010)
Nowadays the common use of biological information in forensic identification not only allows to consider its use as a regular piece of evidence but also opens new perspectives for more complex cases. In any paternity dispute case in which the genetic profiles of the mother (mgt), the child (cgt) and the putative father (pfgt) are available, most of the times, there is no doubt about the use of this kind of evidence. Here the objective is to discuss problems of disputed paternity for which there is no biological information about the putative father. The data sets considered are composed of biological information of the mother, of the child and of one or more individuals genetically related with the putative father. In the cases mentioned here the biological information is obtained from brothers of the putative grandfather. The objective is to compare the only one ancestor cases results and the ones in which it is possible to have more than one ancestor. Although these are not the most common situations there is notice of their occurrence in Portuguese courts.